Adenosine stimulates the basolateral 50 pS K+ channel in renal proximal tubule via adenosine-A1 receptor - Liu, Hao; Sun, Qi; Ding, Zheng; Shi, Wensen; Wang, Wen-Hui; Zhang, Chengbiao (Frontiers in Physiology, 2023)
The basolateral potassium channels play an important role in maintaining the membrane transport in the renal proximal tubules (PT) and adenosine receptors have been shown to regulate the trans-epithelial Na + absorption in the PT. The aim of the present study is to explore whether adenosine also regulates the basolateral K + channel of the PT and to determine the adenosine receptor type and the signaling pathway which mediates the effect of adenosine on the K + channel. Single channel recording has detected a 50 pS inwardly-rectifying K + channel with high channel open probability and this 50 pS K + channel is a predominant type K + channel in the basolateral membrane of the mouse PT. Adding adenosine increased 50 pS K + channel activity in cell-attached patches, defined by NPo (a product of channel Numbers and Open Probability). The adenosineinduced stimulation of the 50 pS K + channel was absent in the PT pretreated with DPCPX, a selective inhibitor of adenosine A1 receptor. In contrast, adenosine was still able to stimulate the 50 pS K + channel in the PT pretreated with CP-66713, a selective adenosine A2 receptor antagonist. This suggests that the stimulatory effect of adenosine on the 50 pS K + channel of the PT was mediated by adenosine-A1 receptor. Moreover, the effect of adenosine on the 50 pS K + channel was blocked in the PT pretreated with U-73122 or Calphostin C, suggesting that adenosine-induced stimulation of the 50 pS K + channels of the PT was due to the activation of phospholipase C (PLC) and protein kinase C (PKC) pathway. In contrast, the inhibition of phospholipase A2 (PLA2) with AACOCF3 or inhibition of protein kinase A (PKA) with H8 failed to block the adenosine-induced stimulation of the 50 pS K + channel of the PT. We conclude that 3 adenosine activates the 50 pS K + channels in the basolateral membrane of PT via adenosine-A1 receptor. Furthermore, the effect of adenosine on the 50 pS K + channel is mediated by PLC-PKC signaling pathway.